A vulnerabilidade dos ativos das Entidades Fechadas de Previdência Complementar nos casos de Fundo de Investimento em Participações sobreprecificado e suas consequências jurídicas - Saraiva Filho, Rômulo Pedrosa (2020)
Closed supplementary pension entities (EFPCs), also called “pension funds”, have their own legislation, which gives them a series of legal characteristics and peculiarities. They have a legal need to diversify their investment portfolio and, for this, they seek the financial market in search of ensuring solvency, liquidity, economic-financial and actuarial balance of their benefit plan. And the Participation Investment Fund (FIP) has attracted the attention of social security entities to allocate resources because of its profitability. The current financial volume in Brazilian pension funds has also attracted people with bad intentions, whether they are internal or external agents of the EFPC. The object of the study analyses the vulnerability of investing in FIP with distorted and overvalued pricing, putting the resources guaranteeing technical reserves and benefits at risk. The fraudulent or reckless management of social security officers assists in making the ruinous investment and entails several consequences and losses for the members who form the social security entity. Participants and beneficiaries, in particular, are most affected, since, as under-paid, the reduction of income due to the solution of the deficit reaches their retirement at a decisive moment in life or they need to increase the value of the social security contribution. The present work points out the legal responsibility in the administrative, criminal and civil spheres of those who gave rise to the damage caused by fraud in the pension fund.